2005
DOI: 10.1021/ja042415g
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of (−)-Isodomoic Acid C

Abstract: The neuroactive algal metabolite (-)-isodomoic acid C, a kainoid amino acid, has been synthesized for the first time. Asymmetric dearomatizing cyclization of an aromatic amide using a chiral lithium amide base generates a bicyclic enone containing a pyrrolidinone ring with the relative and absolute stereochemistry of the target. A further 15 synthetic steps, including conjugate cuprate addition to the enone of a side chain precursor, a Ru-promoted oxidation of the phenyl ring to the C2-carboxylic acid substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 22 publications
1
30
0
1
Order By: Relevance
“…The composition and structure of the obtained isomers of the lactam 7 are confirmed by the data from the 1 H and 13 Under analogous conditions 5% Pd/C and Rh/Al 2 O 3 did not exhibit catalytic activity, and with other reagents reduction either did not occur or a difficultly separated mixture of products was formed. In the presence of 5% Pd/C in boiling formic acid for 2 h formylation occurred at the N-3 atom, and N-formyl-pyrazoline 8 was formed with a yield of 98%.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…The composition and structure of the obtained isomers of the lactam 7 are confirmed by the data from the 1 H and 13 Under analogous conditions 5% Pd/C and Rh/Al 2 O 3 did not exhibit catalytic activity, and with other reagents reduction either did not occur or a difficultly separated mixture of products was formed. In the presence of 5% Pd/C in boiling formic acid for 2 h formylation occurred at the N-3 atom, and N-formyl-pyrazoline 8 was formed with a yield of 98%.…”
supporting
confidence: 52%
“…The latter find use in the synthesis of derivatives of pyrrolidine and analogs of γ-aminobutyric acid -the main neurotransmitter in the central nervous system of mammals [8,9]. The presence of the pyrrolidine ring in the molecule of many natural and synthetic compounds gives rise to a wide range of biological activity [6][7][8][9][10][11][12][13][14][15][16].Recently we showed that 3-aminopyrrolidin-2-one, coupled with a norbornane fragment, exhibits antiarrhythmic, analgesic, nootropic, and anti-inflammatory activity [7].In a continuation of our investigations into the chemistry of pyrazolines [2, 5-7, 17, 18] in the present work we studied the reduction of methyl exo-3,4-diazatricyclo[5.2.1.0 2,6 ]dec-4-ene-5-carboxylate (1) and its 3-methoxycarbonylmethyl-, 3-acetyl-, and 3-nitroso-substituted analogs 2-4 respectively.It should be noted that at the beginning of our researches there were no data in the literature on the synthesis of tricyclic γ-lactams based on derivatives of norbornene.As a result of a search for the optimum reaction conditions for the case of the ester 1 it was established that the most effective of the methods that have widespread application for the reduction of C=N and N=N bonds (H 2 -Raney nickel, H 2 -Pdc, H 2 -PtO 2 , H 2 -Rh/Al 2 O 3 , Na-n-BuOH, RhCl(PPh 3 ) 3 -i-PrOH-KOH, LiAlH 4 , NaBH 4 , NaBH 4 -Cu(acac) 2 ) is hydrogenation with hydrogen in the presence of Raney nickel in _______ …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Opening of lactones of the type represented by 9 with methoxide [41] or MeOH/Et 3 N [42] is known to proceed with low yield because of reversibility. We decided to reduce the lactone.…”
Section: [Ira C H T U N G T R E N N U N G (Cod)mentioning
confidence: 99%
“…Die Abschirmung der Re-Seite des Imins durch die anspruchsvolle 2-Pivaloyloxygruppe des Auxiliars bewirkt eine selektive Bildung des stereogenen Zentrums im Heterocyclus. [8,10,11] Die O-geschützte Alkylseitenkette [12] wird durch konjugierte Addition einer Organokupferverbindung eingeführt. Die besten Ergebnisse wurden mit dem "Komplexreagens" RCu·BF 3 (R = (CH 2 ) 3 OTIPS) erzielt.…”
unclassified